STUDI EFEKTIVITAS PENCAMPURAN SURFAKTAN DENGAN HERBISIDA UNTUK JALUR TANAMAN KARET BELUM MENGHASILKAN - Eko Sulistyono; A. Pieter Lontoh; Hady Widagdo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1999)
The objective of research was to know effective concentration of surfactant and kind of herbicide. Research was conducted at young rubber plantation of PTPN VIII, Sukabumi, West Java. Factorial experiment was arranged in Randomized Block Design with three replication. The first factor was kind of herbicide, glyphosate 2.5 l/ha, sulphosat 1 .5 l/ha and paraquat 2 l/ha. The second factor was surfactant concentration of 0 %, 0.1 % and 0.2 %. Glyphosate that was mixed with 0.2 % of surfactant controlled weed at young rubber plantation effectively. It was showed by low persentage of weed covering. Paraquat without surfactant controlled Borreria alata, and Commelina benghalensis. Glyphosate without surfactant controlled Ottochloa nodosa and Ischaemumti morense.